Context of handball practice and level of integration of fitness capacities to training schedules among players in southern Benin. - NOUATIN, BASILE; GOUTHON, N. M. POLYCARPE; Messan, Folly; DANSOU, HOUNDJOVI PIERRE; AMOUSSOU-GUENOU, KOFFI DANIEL; BIO NIGAN, ISSIAKO; ATTIKLEME, KOSSIVI; GOUDA, SOUAÏBOU L. (My University, 2014)
In the Republic of Benin, the sports results recorded by the clubs and the national handball teams are notsatisfactory. So an inventory of fixtures is essential to identify the factors in cause. This cross-sectional studywas carried out as survey and instrumented observation and aimed at: 1) appreciating the context of competitionhandball practice (CHP) in players from Southern Benin; 2) appreciating the level of integration of physicalcapacities (LIPC) to the training schedule of the players. On the whole, 162 players and 17 trainers filled in twodistinct questionnaires; five training sessions of Division 1 teams were then filmed. The CHP was nonfavourable to the production of good performances in 150 players (46.3%). The LIPCP to training was low in 96players (49.3%), and the juniors among whom it was high were significantly more numerous than the seniors (40versus 26; p= 0.03). LIPCT was also high in 10 trainers out of the 17 surveyed (p = 0.64), but LIPCF was lowfor all the five training sessions filmed. Because the CHP was non-favourable to the performance and the LIPCto their training schedule was low, the fitness capacities and the physiological parameters in matches should beon average of low level in the surveyed players. The results suggest an evaluation of the level of physicalcapacities and physiological responsiveness in the players during matches.
Keywords: Handball; survey; observation; factor of performance; Republic of Benin.